CSU Super Sunday at African-American churches kicks off Feb. 10 - Uribes, Tom::::::::: (2013)
Fresno State officials will visit African American church congregations in Fresno Feb. 10-24 to talk about the importance of college for the 7th annual CSU Super Sunday campaign